2020
DOI: 10.3390/ijms21020618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought Stress during Soybean R2–R6 Growth Stages on Sucrose Metabolism in Leaf and Seed

Abstract: Sucrose is the main photosynthesis product of plants and the fundamental carbon skeleton monomer and energy supply for seed formation and development. Drought stress induces decreased photosynthetic carbon assimilation capacity, and seriously affects seed weight in soybean. However, little is known about the relationship between decreases in soybean seed yield and disruption of sucrose metabolism and transport balance in leaves and seeds during the reproductive stages of crop growth. Three soybean cultivars wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 57 publications
(111 reference statements)
6
70
0
Order By: Relevance
“…In this way, the accumulation of sucrose in sink tissues increases, resulting in a decreased hexose-to-sucrose ratio. In addition, drought stress increases the expression and the activities of acid invertase enzymes in the leaves, leading to irreversible hydrolysis into glucose and fructose [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the accumulation of sucrose in sink tissues increases, resulting in a decreased hexose-to-sucrose ratio. In addition, drought stress increases the expression and the activities of acid invertase enzymes in the leaves, leading to irreversible hydrolysis into glucose and fructose [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants subjected to drought stress usually have accumulated soluble sugars, including sucrose, stored in their source leaves ( Figure 3 ). The accumulation of this stored sucrose in the source leaves act as an imperative energy derivative strategy which improves plant tolerance to drought stress condition [ 142 ]. Interestingly, sucrose could also be accumulated in the leaves if there is a low demand for sucrose at the sink cell [ 136 ].…”
Section: Influence Of Environmental Factors On Photo-assimilate Transportmentioning
confidence: 99%
“…This is an indication of increased capacity of sucrose unloading into seeds and activation of sucrose metabolism during the early seed developmental stage under a drought-stress condition [ 138 ]. However, during late seed-filling stages, basipetal sucrose flow from source leaves to seed decreased, leading to an impaired supply of seed (sink) metabolic need, and thus reduced seed weight or yield [ 142 ]. Since these transporters trigger sucrose export from source leaves to the root (sink), especially during the early plant-developmental stage, enhancing sucrose transport to the root is promising to optimize root development under drought stress [ 138 ].…”
Section: Functional Roles Of Sugar Transporters In Mitigating Environmental Stressmentioning
confidence: 99%
“…Water stress reduced number of full pods per plant by 6.3%, seed yield/plant by 12.8%, and seed size by 6.3% (Table 3). Du et al [13] found that drought prevailing during generative stage, mainly at the middle and late seed filling phases, sucrose movement from leaves to seeds was lessen, and the balance of sucrose metabolism was defected in seeds, rendering in seed mass reduction. Number of full pods per plant and seed size are main attributes of soybean seed yield, the higher the number and the larger the seed size, the higher the yield [14,15,16].…”
Section: Resultsmentioning
confidence: 99%